2012
DOI: 10.1101/gr.138776.112
|View full text |Cite
|
Sign up to set email alerts
|

CpG islands and GC content dictate nucleosome depletion in a transcription-independent manner at mammalian promoters

Abstract: One clear hallmark of mammalian promoters is the presence of CpG islands (CGIs) at more than two-thirds of genes, whereas TATA boxes are only present at a minority of promoters. Using genome-wide approaches, we show that GC content and CGIs are major promoter elements in mammalian cells, able to govern open chromatin conformation and support paused transcription. First, we define three classes of promoters with distinct transcriptional directionality and pausing properties that correlate with their GC content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
180
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(208 citation statements)
references
References 33 publications
26
180
1
1
Order By: Relevance
“…There is evidence for both transcription-independent DNA sequence-driven [48], and transcriptional activity-aided nucleosome organisation [43], suggesting that there might not be a single mechanism responsible for nucleosome positioning at all promoters, but might be dependent on the type of the promoter itself.…”
Section: Mapping Tsss Of Nascent Transcriptsmentioning
confidence: 99%
“…There is evidence for both transcription-independent DNA sequence-driven [48], and transcriptional activity-aided nucleosome organisation [43], suggesting that there might not be a single mechanism responsible for nucleosome positioning at all promoters, but might be dependent on the type of the promoter itself.…”
Section: Mapping Tsss Of Nascent Transcriptsmentioning
confidence: 99%
“…Since the earliest studies on baker's yeast, inquiries into nucleosome positioning have been extended to the genomes of many other organisms, such as Schizosaccharomyces pombe (21) and various other species of yeast (22), Caenorhabditis elegans (23,24), Plasmodium falciparum (25), flies (26), zebrafish (27), Arabidopsis thaliana (28), mice (29,30), and humans (30)(31)(32)(33)(34)(35). Most of these studies were conducted in vivo, and therefore do not allow for isolation of effects encoded into the genomic sequences.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the association between TRs and the expression divergence holds for highly (P < 10 −117 in all organs) and lowly expressed genes (P < 10 −129 in all organs). Second, as CpG islands and promoter GC content have gene regulatory roles through epigenetic mechanisms (Fenouil et al 2012), we asked whether promoters with and without TRs differ in their CpG content. Although we found a small increase in GC in promoters with TRs (WRS, P = 0.02) (Supplemental Fig.…”
Section: The Impact Of Trs On Gene Expressionmentioning
confidence: 99%